Interactional inhospitableness : a re-analysis of the mansplaining incident in Rebecca Solnit’s (2008) essay “Men Explain Things to Me” - Rycker, Teun De (Penerbit Universiti Kebangsaan Malaysia, 2022)
The neologism “mansplaining” refers to a specific type of social behaviour in which “men [are] unnecessarily explaining things to women” (Bridges, 2021, p. 3). With the focus on “unnecessarily,” the verb “to mansplain” calls attention to cases of socio-pragmatic inappropriateness and more specifically to violations of the Gricean Maxim of Quantity. In addition, the creative use of the “man-” morpheme highlights the problematic gendered nature of the phenomenon. This article is an attempt to interpret mansplaining in terms of a notion of interactional inhospitableness. Using a broad-based socio-pragmatic, conversational, discourse-analytical, and praxeological perspective, it will explore the mansplaining interaction (henceforth, the incident) that was recounted and recontextualised in Solnit’s (2008) famous essay, “Men Explain Things to Me: Facts Didn’t Get in Their Way.” The main finding is that though manipulative turn-taking and exploitative epistemic authority played an important role, it was affective asymmetries that made Solnit’s (2008) mansplaining episode uniquely “noticeable.” At the party where the incident occurred, hospitableness and high-culture competition appeared as two defining but conflicting features. This conflict cast the three main participants – not only as reductively gendered interlocutors but – as a failed and failing host (referred to as “Mr. Very Important” in the essay) and two of his guests (Rebecca Solnit and Sallie). The wider relevance and application of a notion of interactional (in)hospitableness will be discussed.